Aspleniaceae endémicas del Perú - León, Blanca (2006)
This family is recognized in Peru by the genus Asplenium and more than 65 species (Tryon & Stolze, 1993; Smith et al., 2005). The Aspleniaceae is represented in a wide range of environments; however the two endemic species are known mainly to occur in the Humid Montane and Premontane Forests regions, between 700 and 2500 m elevation. Only one species is represented in a protected area.